2021
DOI: 10.1038/s41408-021-00487-3
|View full text |Cite
|
Sign up to set email alerts
|

Superior efficacy of co-targeting GFI1/KDM1A and BRD4 against AML and post-MPN secondary AML cells

Abstract: There is an unmet need to overcome nongenetic therapy-resistance to improve outcomes in AML, especially post-myeloproliferative neoplasm (MPN) secondary (s) AML. Studies presented describe effects of genetic knockout, degradation or small molecule targeted-inhibition of GFI1/LSD1 on active enhancers, altering gene-expressions and inducing differentiation and lethality in AML and (MPN) sAML cells. A protein domain-focused CRISPR screen in LSD1 (KDM1A) inhibitor (i) treated AML cells, identified BRD4, MOZ, HDAC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 62 publications
2
28
0
Order By: Relevance
“…However, at the dose and exposure interval of SNDX-50469 utilized in present studies, intracellular depletion of Menin was not observed. Importantly, consistent with previous reports, our findings also confirm that treatment with MI SNDX-50469 induces differentiation, with upregulation of CD11b expression, associated with loss of viability of AML cells harboring MLL1-r and mtNPM1 [ 17 , 26 ]. Consistent with reported effects of DOT1L or DHODH (dihydroorotate dehydrogenase) [ 44 ], these findings indicate that MI treatment also overcomes differentiation blockage in AML cells with MLL1-r [ 17 , 44 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, at the dose and exposure interval of SNDX-50469 utilized in present studies, intracellular depletion of Menin was not observed. Importantly, consistent with previous reports, our findings also confirm that treatment with MI SNDX-50469 induces differentiation, with upregulation of CD11b expression, associated with loss of viability of AML cells harboring MLL1-r and mtNPM1 [ 17 , 26 ]. Consistent with reported effects of DOT1L or DHODH (dihydroorotate dehydrogenase) [ 44 ], these findings indicate that MI treatment also overcomes differentiation blockage in AML cells with MLL1-r [ 17 , 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…1 B, C). We also employed the dTAG-13 system to degrade Menin-FKBP12 F36V in MOLM13 cells, following near-complete KO of the endogenous Menin, to assess biologic effects in MOLM13 cells ectopically transduced with and expressing Menin-FKBP12 F36V [ 26 ]. A near-complete KO of the endogenous Menin was achieved by transducing two splice-blocking sgRNAs, one in the intron between exon 3 and exon 4 and the other in the intron between exon 5 and exon 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar approaches have also revealed metabolic genes capable of influencing cellular commitment to apoptosis and sensitizing AML cells to venetoclax [ 82 , 85 ]. Finally, CRISPR high-throughput approaches have anticipated gene determinants to enhance the sensitivity of small molecules under development for AML treatment [ 45 , 73 , 242 ].…”
Section: Hematologic Dependency Map Through Crispr Screens: Essential...mentioning
confidence: 99%
“…Prior work from our lab and others suggest that the combination of kinase and LSD1 inhibition may be an effective therapeutic strategy in AML (20)(21)(22)(23). To establish whether this approach is effective for FLT3-ITD AML, we treated FLT3-ITD-positive (MOLM13 and MV4-11) and FLT3-ITD-negative (K562) cell lines with multiple FLT3/LSD1 inhibitors.…”
Section: Combined Flt3/lsd1 Inhibition Synergistically Represses Myc ...mentioning
confidence: 99%